GAMBARAN PERKEMBANGAN BALITA STUNTING DI DESA WUNUNG WILAYAH KERJA PUSKESMAS WONOSARI I GUNUNG KIDUL YOGYAKARTA - Rizky Syahputri, Silvia; Yuni Astuti Anggraini, Tyasning (Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: Indonesia still experiences various health and nutrient problem. On susceptible group of mother and child, the high rate of short toddler prevalence which is 37.2% becomes one of national development priorities. It is included in the main objective of intermediate development year 2015-2019. They village of Wunung highest stunting prevalency in Yogyakarta. Amount of research show binding between stunting with motorist development and toddler's mental. Objective: To find out the development picture on stunting toddler In Wunung Village In The Work Region Of Wonosari I Primary Health Center Gunungkidul Yogyakarta. Research method: This research is in the form of descriptive-quantitative research. This research used non random sampling, purposive, method with 45 samples. Result: The result of the research is not in accordance with the theory which suggests that the stunting affects the toddler development. It is because development has many factors. One of them is psycho-social factor which includes stimulant, learning motivation and peer group. In Addition 60% of average 36 months toddler have been sent to pre school in which they get stimulant, learning motivation and peer group. Conclusion: The result of the research shows that most stunting toddlers; 32 toddlers (71.1%); have normal development. 12 toddlers (26.75%) have dubious development while 1 toddler (2.2%) has deviate development. Keyword: Stunting toddler, development.